2010
DOI: 10.1200/jco.2009.26.5785
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Study of Imatinib Plasma Trough Levels in Patients With Advanced Gastrointestinal Stromal Tumors: Impact of Gastrointestinal Resection on Exposure to Imatinib

Abstract: In patients with GIST, imatinib C(min) at steady state was significantly associated with albumin concentration, creatinine clearance, and previous major gastrectomy. Although its clinical impact is unclear at present time, monitoring of imatinib C(min) might be particularly important for optimal treatment with imatinib in patients who have undergone major gastrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
71
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 23 publications
12
71
3
Order By: Relevance
“…A plasma concentration below 1,100 ng/mL has been associated with short time to disease progression in patients with unresectable/metastatic GIST [19] . The inter-patient variability in imatinib pharmacokinetics seems to be significant, and the trough level (C min ) has been significantly associated with albumin concentration, creatinine clearance and major gastrectomi but not to previous grades 3 to 4 toxicity in patients taken a standard dose of 400 mg daily [18] . Except for patients with KIT exon 9 mutations, 400 mg daily is the standard dose for treatment of high-risk GIST regardless of the patient's gender, age or body mass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A plasma concentration below 1,100 ng/mL has been associated with short time to disease progression in patients with unresectable/metastatic GIST [19] . The inter-patient variability in imatinib pharmacokinetics seems to be significant, and the trough level (C min ) has been significantly associated with albumin concentration, creatinine clearance and major gastrectomi but not to previous grades 3 to 4 toxicity in patients taken a standard dose of 400 mg daily [18] . Except for patients with KIT exon 9 mutations, 400 mg daily is the standard dose for treatment of high-risk GIST regardless of the patient's gender, age or body mass.…”
Section: Discussionmentioning
confidence: 99%
“…Doubling the dosage of imatinib from the standard level (400 mg daily) to a high dose (400 mg twice daily) increases the incidence of severe adverse events [13,17]. However, no correlation could be seen between imatinib plasma trough level and previous grade 3 to 4 toxicity in patients taken a standard dose of 400 mg daily, but there was a significant correlation to plasma albumin and creatinine clearance [18]. Low plasma concentrations of imatinib have been associated with a shortened time to disease progression [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior surgery plays a substantial role in the bioavailability of TKI therapy, as all compounds currently used in the treatment of GIST are taken orally. Imatinib has an acid-dependent solubility, and plasma concentrations are significantly lower in patients who have undergone gastrectomy as part of prior GIST resection surgery (Yoo, 2010). Additionally, genetic polymorphisms affecting cellular uptake of imatinib have been shown to be important in CML patients.…”
Section: Pharmacokinetic Considerations Of Therapymentioning
confidence: 99%
“…Subsequent pharmacokinetic studies failed to confirm this, either because repeat pharmacokinetic studies were conducted too early, for example, at 4 weeks in the case of the study by Demetri and colleagues (7), or because the study was conducted in patients who had been on treatment for varying periods of time, that is, a cross-sectional, rather than a prospective evaluation. For example, in the case of the cross-sectional study reported by Yoo and colleagues (11), most of the patients had already been on treatment for 5 months or more at the time of pharmacokinetic analysis; hence, any increase in clearance with time might already have occurred. However, this study did report some important findings, including reduced imatinib trough levels in patients who had had a major gastric resection and an association between imatinib clearance and albumin levels, as previously suggested (9).…”
mentioning
confidence: 99%